Peranan Dan Fungsi Sistem Informasi Manajemen Rumah Sakit (SIMRS): Tinjauan Teoritis - Mahmud Hakim; Dety Mulyanti (Prodi D3 Farmasi Politeknik Katolik Mangunwijaya, 2023)
The hospital is a health service institution that provides comprehensive individual and group health services that provide inpatient, outpatient and emergency services. Hospital services cannot be separated from the hospital management information system (HMIS). HMIS is part of a health information system in the form of a network of coordination, reporting and administrative procedures to obtain precise and accurate information. The purpose of this theoretical review is to find out how the role and function of the hospital information management system are. The method used is a theoretical review by analyzing and comparing existing theories. The results of this theoretical review are to support community management in order to improve health services for the whole community whose role is to improve service efficiency, finance, health facilities, inventory, staff, information and data integration. It can be concluded that HIMS is an important instrument in the operation of a hospital in modern times. So that the process of collecting, processing, and presenting data about hospitals can be done much easier. In its role and function, HIMS is integrated and systematic and improves service quality, maintains good and correct standards of medical practice and becomes a very effective coordinating tool.